Polyaniline-SrTiO3 nanocube based binary nanocomposite as highly stable electrode material for high performance supercapaterry. Issue 9 (15th June 2019) - Shahabuddin, Syed; Numan, Arshid; Shahid, Muhammad Mehmood; Khanam, Rashmin; Saidur, R.; Pandey, A.K.; Ramesh, S.
Abstract: The current study demonstrates the simplistic approach for the synthesis of SrTiO3 nanocubes incorporated polyaniline flakes (PANI-SrTiO3 ) by facile in-situ oxidative polymerisation route. The synthesised nanocomposites were characterised by various spectroscopic and surface analysis techniques viz. X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), thermogravimetric analysis (TGA), and Brunauer-Emmett-Teller analysis (BET). The electrochemical performance of the prepared nanocomposites for energy storage application was evaluated by electrochemical impedance spectroscopy (EIS), galvanostatic charge-discharge (GCD) and cyclic voltammetry (CV) in 1 M of KOH as an electrolyte. The electrochemical investigations demonstrate that the performance of the PANI-SrTiO3 nanocomposite in terms of rate capability was significantly higher as compared to the polyaniline flakes and SrTiO3 nanocubes. Supercapattery was fabricated by combining activated carbon and PANI-SrTiO3 -250 as negative and positive electrodes respectively in order to evaluate complete device performance. It is found that fabricated supercapattery gave an energy density of 13.2 W h/kg at a power density of 299 W/kg. Additionally, the fabricated supercapattery also offered excellent stability cycle with 114% capacity retention after 4000 cycles. Moreover, the performance of PANI-SrTiO3 -250 was found to be better than the other compositions.